Beneficial effects of combined resveratrol and metformin therapy in treating diet‐induced insulin resistance. Issue 15 (1st August 2016) - Frendo‐Cumbo, Scott; MacPherson, Rebecca E. K.; Wright, David C.
Abstract: The polyphenol compound resveratrol (RSV) has attracted attention due to its reputed beneficial effects on insulin sensitivity. Our lab has previously identified protective effects of RSV against the development of type 2 diabetes in rats. These effects occurred in a manner similar to thiazolidinedione's (TZDs), a class of insulin sensitizing drugs. TZDs are commonly prescribed in combination with metformin (MET) and thus we sought to examine the combined effects of RSV and MET in treating insulin resistance. Male C57BL6 mice were fed a low‐ (LFD; 10% Kcal from fat) or high‐fat diet (HFD; 60% Kcal from fat) for 9 weeks to induce glucose and insulin intolerance. HFD mice were then assigned to control (HFD), MET (231.28 ± 12.24 mg/kg/day), RSV (93.68 ± 3.51 mg/kg/day), or combined (COM; MET 232.01 ± 17.12 mg/kg/day and RSV 92.77 ± 6.92 mg/kg/day) treatment groups. Changes in glucose and insulin tolerance and tissue‐specific insulin signaling were measured 4 weeks post‐treatment. RSV or MET alone did not have beneficial effects on glucose tolerance, although MET significantly improved insulin tolerance compared to HFD. Glucose and insulin tolerance were significantly improved in COM compared to HFD and this was mirrored by enhanced insulin‐stimulated AKT phosphorylation in triceps muscle and inguinal subcutaneous adipose tissue in COM compared to HFD mice. Improvements with COM treatment were not explained by differences in body weight, adiposity, or markers of adipose tissue inflammation. In summary, this study provides evidence of beneficial effects of combined RSV and MET therapy in treating impairments in glucose homeostasis. Abstract : We have compared the individual and combined effects of resveratrol and metformin in treating insulin resistance. Dual therapy treatment led to improvements in glucose tolerance that was associated with increases in insulin signalling in subcutaneous adipose tissue.